Leveling the playing field in youth basketball: How compensatory training with small-sided games enhances physical fitness and reduces relative age effect bias in match selection - Li, M.; Zeng, Y.; Wei, L.; Li, J. (Journal of Sports Science & Medicine, 2025)
The purpose of this study was to analyze the effects of compensatory training on later-born basketball players, who had less match time compared to their peers, focusing on their physical fitness and skill development. A prospective cohort study compared three groups of male youth basketball players (ages 12-14). One group consisted of later-born players with a high volume of match play in competitive scenarios (lbHPT), while the other two groups had match play below the median of the teams. Among these two groups, one received compensatory training (lbLPTcomp), and the other did not (lbLPTreg). Players were evaluated at three time points: baseline, 3 months, and 6 months. The assessments measured aerobic capacity (using the Yo-Yo intermittent recovery test), 10-meter sprint performance, 5-0-5 change of direction (COD deficit), and performance on the basketball technical test (LSPT). The compensatory training consisted of two weekly sessions in which, after regular training, the later-born players participated in 2v2 or 3v3 small-sided games lasting 15 minutes per session. The results revealed that lbLPTcomp was significantly effective in reducing the differences with lbHPT, as no significant differences were observed between the two cohorts over the 6 months for any of the outcomes (p > 0.05). Additionally, lbLPTcomp performed significantly better than lbLPTreg post-6 months in the LSPT (p = 0.033) and COD deficit (p = 0.003). The lbLPTreg group was also significantly worse than lbHPT in the YYIRT (p = 0.022), LSPT (p = 0.036), and COD deficit (p = 0.005). No significant between-group differences were found in 10-m sprint after 6 months (p = 0.241), though lbHPT and lbLPTcomp improved significantly (both p < 0.001). In conclusion, while compensatory training like twice-weekly small-sided games may help later-born youth athletes with limited playtime, further research is needed before broad implementation.